2020
DOI: 10.4236/aim.2020.102004
|View full text |Cite
|
Sign up to set email alerts
|

Edible Growth Medium: A New Window for Probiotic Research

Abstract: Conventional growth media for microbes contains lots of non-edible components that are harmful to consume when the organism is ready to intake-like probiotics growing in chemical media (Lactobacillus grown in MRS media). The study was conducted to develop an edible and low-cost growth media that supports the growth of probiotics Lactic Acid bacteria for the enhancement of probiotic research. The 04 isolates of Lactobacillus (L. plantarum, L. rhamnosus, L. ferciminis and L. bifarmentans) and 02 Bifidobacterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…and Bifidobacteria sp. [27]. In agreement with these results was the cultivable community structure of bacteria identified from both root and inner tissues of maize as well as rice seedlings [59,60].…”
Section: Discussionsupporting
confidence: 77%
“…and Bifidobacteria sp. [27]. In agreement with these results was the cultivable community structure of bacteria identified from both root and inner tissues of maize as well as rice seedlings [59,60].…”
Section: Discussionsupporting
confidence: 77%
“…Conversely, LAB cultured in almond broth exhibited the lowest cell viability (0.90 ± 0.02 × 10 8 CFU/mL). The superior performance of mung bean and coconut media can be attributed to their higher carbohydrate content than other plant-based media (Hossain et al 2020). Additionally, our results showed that GABA produced by LAB cultured in these media was lower than in MRS broth.…”
Section: Effect Of Fermentation Of Co-cultured Lab In Different Types...mentioning
confidence: 64%
“…bulgaricus warrants supplementing the growth media with amino acids, peptides and vitamins, hence, yeast extracts are recommended as complex nitrogen sources for growth promotion (Atilola et al , 2015; Curk et al ., 1993; Klotz et al ., 2017). Bacterial growth in the MRS and KCMax media blends suggested their nitrogen content impacted bacterial growth (Hossain et al ., 2020; Papizadeh et al , 2020). Generally, nutritional requirements for LAB growth are strain-dependent (Degeest and De Vuyst 1999; Saguir and de Nadra, 2007), thus, alternative yeast extracts (X-Seed Nucleo Max, KAT, and Carbo Max) in the optimized medium demonstrated promising results as compared to conventional MRS. A basal medium (2 g/l of X-Seed Nucleo Max: N-Max) with KCMax (10/10) i.e.…”
Section: Resultsmentioning
confidence: 99%